PEMANTAUAN PH KOLAM IKAN HIAS BERBASIS IOT MENGGUNAKAN METODE FUZZY LOGIC - Kusdarnowo Hantoro; Asep Ramdhani Mahbub; Bagus Iqbal Satria (Fakultas Ilmu Komputer dan Desain - Unsurya, 2024)
From year to year, koi fish enthusiats certainly impact koi fish farmers to meet the increasing market demand. For now, the biggest problem for farmers is the difficulty of reducing mortality in koi fish seeds that are susceptible to disease because of the lack of monitoring of pH and water temperature. Besides that, time constraints are also a major factor for cultivators and hobbyists to monitor the pH and temperature of the koi fish pond water. The research aims to make a pool check that can be monitored through the website. This application is designed using an ESP32 microcontroller which is connected to a computer using the Arduino IDE application based on the internet of things (IoT). From this research, it is hoped that it will make it easier for koi fish cultivators and hobbyists to care for and monitor the pH and temperature of the koi pond water, so as to reduce mortality in fish seeds and use time because they can supervise when outside the home or wherever they are. Â Keywords: monitoring pH, temperature, sensors, pools, IoT